Role of Circulatory Hypoxia in the Development of Retinopathy of Prematurity - E. I. Sidorenko; G. V. Nikolaeva; E. E. Sidorenko (Oftalʹmologiâ, 2018)
Purpose: to study the pathogenesis of retinopathy of prematurity.Patients and methods. 642 preterm infants born before 30 weeks  gestation with the weight less 1500 grams were examined. The  study included: indirect ophthalmoscopy; digital retinoscopy; calibrometry of retinal vessels; dopplerography;  analysis of partial pressure of oxygen and carbon dioxide in the  capillary blood. Results. The first phase of retinopathy of prematurity (ROP)  occurred due to the immaturity of the mechanisms of autoregulation  of the blood flow and the inadequate reaction of immature retinal  vessels to oxygen. It was established: the less gestational age of a  child, so there are less mechanisms of autoregulation of  hemodynamics. The perverse reaction of autoregulation leads to  pronounced arteriospasm, increasing the zone of hypoxia, and  triggering pathological angiogenesis. In morphologically immature  children, arteriospasm of retina vessels is more often detected, and  narrowing degree of vessels is higher. Arteriospasm is defined in 82  % of children born at the age of gestation from 25 to 27 weeks, in  67 % — at a period from 28 to 29 weeks, in 54 % — from 30 to 32  weeks. In children with ROP in the preclinical period of the disease,  retinal angiospasm is noted at values of pO2 in capillary blood less  then 40 mm Hg or exceeding the upper limit of the norm values of  pCO2 (the norm values of pO2 are 40–60 mmHg, pCO2 are 35–45  mm Hg). Autoregulation of blood flow is immature and inadequate.  In the group before 30 weeks of post-conceptual gestational age  without development of ROP, a spastic reaction of retinal arteries  was revealed at the background of subnormal pO2 values in capillary  blood. Biochemical autoregulation of blood flow is still  immature. But from the 30 week of post-conceptual gestational age  arteriospasm of retina is formed at values of pO2 of 45 mm Hg or  higher (p < 0.05). The normal caliber of retinal arteries in children  without development of ROP is revealed at the background of mean  values of pO2 below 45 mm Hg and values of pCO2 below 42 mm Hg before 30 weeks of post-conceptual gestational age, and above 45  mm Hg from the 30th week of post-conceptual gestational age. In children without ROP from 30 weeks of gestational age biochemical  autoregulation of blood flow functions. It is important the degree of  an angiospasm for the development of ROP. Dopplerographic critical  index of blood flow disturbance in the ophthalmic and anterior cerebral arteries has been established — the index of resistance (IR)  exceeding 0.8. It is a precursor of the development of ROP and pathological angiogenesis. In the group of children with ROP, the IR  of the anterior cerebral artery is 0.84 ± 0.02 (in av.). The IR of the  ocular artery was 0.83 ± 0.03. In higher index (up to 0.9–1), the  process in the eye was more active.